How pandemic and sustainability concerns transform the office market - a case study of Budapest, Hungary - Huszár, Barbara E.; Soóki-Tóth, Gábor (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
Major forces are transforming the office real estate market globally. One such force is the COVID-19 pandemic, which triggered a substantial growth in remote work. Another can be found in environmental concerns that demand sustainable buildings and operations. A third is the increasing emphasis on the health and safety concerns regarding buildings. A fourth is the changingeconomic/geopolitical landscape. The purpose of this paper is to evaluate the relationship between the increasing emphasis on remote work (partially as a result of COVID-19), environmental sustainability for buildings and office space, and larger financial concerns and the types and sizes of leasing and purchasing transactions for green-certified and non-green-certified spacesin Budapest before, during, and after the global pandemic. The goal of the research is to map the office tenants’ size optimization attitudes since the global pandemic outburst. The research aimed to understand how the Budapest office market reacted to the global pandemic, with particular emphasis on green-certified office space. The research examined Budapest office market leasingtransactions between 2018 and 2022 by way of a statistical analysis and individual interviews with market actors. Results show that after a small decrease in 2020, the average, green-certified transaction size increased in 2021; however, it showed a 13% decrease in 2022. In the case of not green-certified offices, the average transaction size decreased for 2 years, but in 2022, increased by60%. Market actors see a large demand from multinational companies for green offices, as environmental, social, and governance (ESG) policies drive corporations; however, there are financial pressures at play, which motivate tenants to optimize their space decisions.